2016
DOI: 10.1002/jrs.5050
|View full text |Cite
|
Sign up to set email alerts
|

A spectroelectrochemical investigation of nanoparticle and molecular resonances in surface enhanced Raman scattering from crystal violet and malachite green

Abstract: The interaction between nanoparticle plasmonic states and molecular electronic states is central to the large enhancements observed in surface‐enhanced Raman scattering (SERS). In this work, we use a model previously used in a fully quantum mechanical description of SERS to explain the enhancement of nontotally symmetric modes for crystal violet (CV) and malachite green (MG) adsorbed on silver nanoparticles. Our explanation is consistent with recent observations of the absorption spectra of dyes on silver nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…To investigate the SERS enhancement capabilities of the HPMS and NPoM platforms, we determined the analytical enhancement factor (AEF) by using the ring C–H in-plane vibrational mode of malachite green (MG) at 1173 cm –1 . Because the UV–vis absorption peak of malachite green is distributed in the range of 300–670 nm and there is no absorption peak around 785 nm, it will not be in resonance with the laser (785 nm) utilized for the SERS measurements . Thus, MG is an appropriate Raman label to evaluate the AEF of the HPMS and NPoM platforms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the SERS enhancement capabilities of the HPMS and NPoM platforms, we determined the analytical enhancement factor (AEF) by using the ring C–H in-plane vibrational mode of malachite green (MG) at 1173 cm –1 . Because the UV–vis absorption peak of malachite green is distributed in the range of 300–670 nm and there is no absorption peak around 785 nm, it will not be in resonance with the laser (785 nm) utilized for the SERS measurements . Thus, MG is an appropriate Raman label to evaluate the AEF of the HPMS and NPoM platforms.…”
Section: Resultsmentioning
confidence: 99%
“…27 Because the UV−vis absorption peak of malachite green is distributed in the range of 300−670 nm and there is no absorption peak around 785 nm, it will not be in resonance with the laser (785 nm) utilized for the SERS measurements. 28 Thus, MG is an appropriate Raman label to evaluate the AEF of the HPMS and NPoM platforms. The detailed peak assignment is listed in Table S1.…”
Section: Fabrication Of a Self-confine And Npom Sersmentioning
confidence: 99%
“…Their spectroelectrochemical data showed that SERS intensities from silver nanoparticles can be optimized with appropriately applied potentials. Their work also highlighted the need for more detailed studies of the spectroelectrochemistry of dyes adsorbed on silver nanoparticles to more fully understand how SERS intensities respond to applied potentials . Filho, Cunha, and Rivelino studied the SERS properties of the Lewis acid‐base (LA‐LB) complexes of p‐hydroxybenzoic and p‐mercaptobenzoic acids with CO 2 in the presence of silver.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…Their work also highlighted the need for more detailed studies of the spectroelectrochemistry of dyes adsorbed on silver nanoparticles to more fully understand how SERS intensities respond to applied potentials. [25] Filho, Cunha, and Rivelino studied the SERS properties of the Lewis acid-base (LA-LB) complexes of p-hydroxybenzoic and p-mercaptobenzoic acids with CO 2 in the presence of silver. Their work demonstrated that the lowest singlet π-π* excitation of both LA-LB complexes is significantly red-shifted, which gives evidence for such a complexation with CO 2 .…”
Section: Sers Substratesmentioning
confidence: 99%
“…9 The enhancement mechanism is mainly related to the large enhancement of electromagnetic field due to the surface plasmon resonance (SPR) of metal nanostructures or nanoparticles. 10 A typical SERS system considers the adsorption of molecules on the nanoparticle state of coinage metals, such as copper, silver, and gold. 11,12 Au nanoparticles (AuNPs) are often used as SERS substrates because of the SPR enhancement effect and special stability.…”
mentioning
confidence: 99%